Classroom Techniques Used In Teaching Speaking at SMK Muhammadiyah 1 Sukoharjo In 2016/2017 Academic Year - Dwi Saputri, Pipit; , Nur Hidayat, M.Pd (2017)
SUMMARY PIPIT DWI SAPUTRI. A320120197. CLASSROOM TECHNIQUES USED IN TEACHING SPEAKING AT SMK MUHAMMADIYAH 1 SUKOHARJO IN 2016/2017 ACADEMIC YEAR. RESEARCH PAPER. SCHOOL OF TEACHER TRAINING AND EDUCATION. MUHAMMADIYAH UNIVERSITY OF SURAKARTA. This research describes the types of technique used by the English teacher of SMA N 2 Sukoharjo to develop students' English speaking skill, classroom procedure, probem faced by teacher, and problem faced by students. The type of this research is descriptive qualitative. The methods of colleting data in this research are: observation, interview, and documentation. The result shows that the techniques used by the English teacher in teaching learning process to develop students' speaking skill at SMK Muhammadiyah 1 Sukoharjo are Role-play, Discussion, Picture Describing and Brainstorming. Various techniques used by the teacher in teaching learning process make the student more active, more creative and the enthusiastic in teaching learning process especially in speaking activity in the classroom. Various techniques also make the student not bored when learning process, the students' fun, enjoyed and confident when learning speaking process. Based on the observation, the use of technique in teaching learning process is very important to make situation in classroom more interesting and make the student enthusiastic in learning process. Key Words : Classroom Techniques in Teaching Speaking, Classroom Procedure, Problem Faced by Teaching, Problem Faced by Students